Status inequalities within families in relation to their structural differences - Hannan, D (Economic & Social Studies, 1970)
The nuclear family, not the individual, is regarded as the basic unit of social stratification systems: a nuclear family being usually defined as a man and wife, with their dependent children, sharing a common domicile. All members of this household share the same status in the eyes of the community, dependent children being accorded the status of their parents. When the children assume an independent occupational or familial role, and especially when they take up a separate residence of their own, their status comes to depend primarily on their own characteristics and their own achievements.1 Relative to his father's position the individual can move to a higher status, hold the same position, or move to a lower one. To measure this relative mobility the occupation of the father and of his son (once he has established an independent occupational role) is used as the basic indicator of status or prestige position.2
Keywords: Economics; Sociology